2009
DOI: 10.1186/1471-2334-9-47
|View full text |Cite
|
Sign up to set email alerts
|

Serum markers in interstitial pneumonia with and without Pneumocystis jiroveciicolonization: a prospective study

Abstract: BackgroundIn patients with chronic respiratory disease, Pneumocystis jirovecii (P. jirovecii) colonization is observed, and may influence disease progression and systemic inflammation. Pneumocystis pneumonia causes interstitial changes, so making a diagnosis of PCP in patients who have interstitial pneumonia (IP) with P. jirovecii colonization is sometimes difficult based on radiography.MethodsThis study investigated the prevalence of P. jirovecii colonization in IP patients and assessed pulmonary injury due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
24
0
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 34 publications
1
24
0
7
Order By: Relevance
“…The remaining two patients presented positive BG results but with values (82.7 and 84 pg/ml) close to the threshold (24). Similarly, Shimizu et al showed that serum BG levels determined using the Wako test kit (Wako Pure Chemical Industries, Tokyo, Japan; manufacturer's threshold, Ն11 pg/ml) were negative for 7 of 7 colonized patients (25). Using the same assay with a threshold adjusted to 15.6 pg/ml, Matsumura et al determined a specificity of 80% and a sensitivity of 100% for PCP diagnosis with the serum BG assay (26).…”
mentioning
confidence: 99%
“…The remaining two patients presented positive BG results but with values (82.7 and 84 pg/ml) close to the threshold (24). Similarly, Shimizu et al showed that serum BG levels determined using the Wako test kit (Wako Pure Chemical Industries, Tokyo, Japan; manufacturer's threshold, Ն11 pg/ml) were negative for 7 of 7 colonized patients (25). Using the same assay with a threshold adjusted to 15.6 pg/ml, Matsumura et al determined a specificity of 80% and a sensitivity of 100% for PCP diagnosis with the serum BG assay (26).…”
mentioning
confidence: 99%
“…Its clinical usefulness had been demonstrated with hematologic patients when used either alone (13) or in combination with serum galactomannan (9). BG is also a component of the P. jiroveci cell wall, but no method for detecting BG in serum has so far been validated for diagnostic purposes in PCP, despite some encouraging reports (3,10,14).The aim of this study was to evaluate the role of a serum BG test in the presumptive diagnosis of PCP in immunocompromised patients unable to undergo invasive diagnostic procedures.From May 2008 to January 2009, 31 serum samples from immunocompromised patients with pneumonia were collected and stored. All patients admitted to our clinical unit and for whom invasive diagnostic procedures were unfeasible had clear risk factors (see below) for PCP.…”
mentioning
confidence: 99%
“…Its clinical usefulness had been demonstrated with hematologic patients when used either alone (13) or in combination with serum galactomannan (9). BG is also a component of the P. jiroveci cell wall, but no method for detecting BG in serum has so far been validated for diagnostic purposes in PCP, despite some encouraging reports (3,10,14).…”
mentioning
confidence: 99%
“…Furthermore, 36% of IPF patients grow bacteria in BAL fluid in the absence of clear signs of infection, even before immunosuppression [55]. A specific role for co-trimoxazole is also suggested by a high prevalence of P. jiroveci colonization (23.3%) among patients with IPF associated with collagen vascular disease [56]. The importance of infection is outlined by the findings of the TIPAC study; 11/35 deaths were a result of pneumonia during the study [57].…”
Section: Management Strategiesmentioning
confidence: 99%